Fenomena Perceraian Pada Keluarga Muslim di Kabupaten Cirebon - Sukardi, Didi; Rana, Mohamad (Mahkamah : Jurnal Kajian Hukum Islam, 2024)
This study aims to analyze the factors that cause the high rate of divorce in Muslim families in Cirebon Regency. This is based on the data from the annual report issued by the Sumber Religious Court. In addition, this study seeks to find solutions to minimize divorce rates. In this study, the method used is descriptive analysis with a sociological approach to law. The data collection techniques in this study were conducted using interviews with parties who filed for divorce, interviews with judges of the Sumber Religious Court and BP4, and literature studies. The results showed that factors of disharmony, economic problems, factors of no responsibility, the presence of third persons, factors of immoral acts, and factors of domestic violence caused the high divorce rate in Cirebon Regency. Solutive efforts to minimize the divorce rate in Cirebon Regency are by reconstructing mediation rules, reviving the role of BP4, maximizing premarital guidance, and making family resilience program policies.